Free vibration characteristics of glass and bamboo epoxy laminates under hygrothermal effect: A comparative approach. (1st November 2019) - Sit, Moumita; Ray, Chaitali
Abstract: The present paper attempts to identify the suitability of natural fibre composite as a potential substitute of conventional synthetic fibre reinforced composite materials. Experimental and numerical models are developed to study the variation of vibration characteristics and other engineering properties of both types of laminates in hygrothermal environment. A finite element model based on Green–Lagrange type nonlinear third order shear deformation theory is developed to account for the nonlinear behaviour induced due to hygrothermal effect. A computer code is developed using MATLAB. The laminates are prepared in the laboratory by adopting vacuum bagging technique. The present numerical model is validated by comparing the solutions with experimental results. A comparative study in the perspective of hygrothermal effects on dynamic characteristics of glass fibre reinforced polymer (GFRP) composites and bamboo mat reinforced polymer (BMRP) composites is carried out. The study reveals that the vibration characteristics of BMRP laminates are comparable to glass fibre reinforced plastic (GFRP) laminates even in elevated temperature and moisture.